From the Spoken to the Written Word: An Account of Pre-Twentieth Century Literacy in England - AZOUI, Samih (Journal of Human Sciences, 2009)
This article looks at literacy in England from Roman times to the close of the nineteenth century. By exploring the changing significance of literacy and its spread among the different social classes, the article is intended to offer a contribution to a better understanding of the impact of literacy on the unfolding of the social history of England.